Bibliometric review of research on green building assessment method by CiteSpace and HistCite - Li, Yuanyuan; Wang, Ying; Wang, Rui; Liu, Chunlu; Zhang, Zhigang (International Journal of Strategic Property Management, 2024)
Numerous qualitative review studies have been conducted to enhance the understanding of current research status of green buildings (GBs). Green building assessment methods (GBAMs) are crucial to the development of GBs and relevant research works has received wide attention. However, there are very few reviews to quantitively explore these studies. Therefore, this paper aims to systematically review literatures on GBAMs, and visually analyzes them through CiteSpace and HistCite. The article identified the most influential journals, contributors, representative institutions and regions. The knowledge bases of this area focus on “triple bottom line”, “indicator”, “building design”, “life cycle costing”, “life cycle sustainability assessment”, “tropical climate”, “building information modelling” and “Chinese green building label”. Through citation analysis, “updating existing GBAMs by scheme comparison”, “updating existing GBAMs by GB case analysis”, “establishment of new GBAMs” and “incorporation of BIM in GBAMs” were found as the main research themes. “Design”, “LCA”, “model”, “energy”, “management”, “residential buildings” and “office buildings” are high-frequency keywords. Future research directions were finally proposed as “more investigation on the other types of GBs”, “incorporation of cost-related criteria”, “enhancing health-related indicators” and“integrating with BIM technology”. The results could provide a useful reference to industry practitioners and scholars interested in GBAMs.